2008
DOI: 10.1074/jbc.m709118200
|View full text |Cite
|
Sign up to set email alerts
|

RNaseE and RNA Helicase B Play Central Roles in the Cytoskeletal Organization of the RNA Degradosome

Abstract: The RNA degradosome of Escherichia coli is a multiprotein complex that plays an essential role in normal RNA processing and decay. It was recently shown that the major degradosome constituents are organized in a coiled cytoskeletal-like structure that extends along the length of the cell. Here we show that the endoribonuclease E (RNaseE) and RNA helicase B (RhlB) components of the degradosome can each independently form coiled structures in the absence of the other degradosome proteins. In contrast, the cytosk… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
53
0

Year Published

2009
2009
2014
2014

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(58 citation statements)
references
References 35 publications
5
53
0
Order By: Relevance
“…3G). This pattern was reminiscent of many helical patterns present in bacterial cells (20,(22)(23)(24)(25)(26)(27)(28). Note, however, that these RNArelated patterns were more diffuse than most helical patterns revealed by protein labeling.…”
Section: Estimation Of Number Of Egfp Molecules Per Cell After Rna Inmentioning
confidence: 84%
See 2 more Smart Citations
“…3G). This pattern was reminiscent of many helical patterns present in bacterial cells (20,(22)(23)(24)(25)(26)(27)(28). Note, however, that these RNArelated patterns were more diffuse than most helical patterns revealed by protein labeling.…”
Section: Estimation Of Number Of Egfp Molecules Per Cell After Rna Inmentioning
confidence: 84%
“…These structures are independent of the MreB and MinD cytoskeletal structures and may play important roles in cell growth, division, and chromosome segregation. They may also serve to compartmentalize RNA processing and RNA degradation (27,28). It is tempting to speculate that the RNA network that we are revealing may be related to the same structures.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Using similar techniques, Shih et al then reported that MreB (and three other proteins) formed extended helices in Escherichia coli as well (27). Numerous publications have since claimed that MreB and various other proteins polymerize into extended helices that encircle diverse rod-shaped bacteria (5,8,15,22,30,31,36). Data supporting these claims include fluorescence microscopy of both cells harboring fluorescent protein fusions and wild-type cells probed with fluorescently labeled antibodies.…”
mentioning
confidence: 84%
“…RNase E and other degradosome components are associated with the inner surface of the cell (110), interact with the bacterial cytoskeleton (111,112) and the inner membrane (113). RNase Y has a transmembrane domain at its N-terminus and has been localized at the membrane in vivo (81).…”
Section: Multiprotein Complexes and Cellular Localizationmentioning
confidence: 99%